Karakteristik Perempuan Madyan Dalam Kisah Nabi Musa A.S. (Analisis Tematik Q.S. al-Qashash Ayat 23-28) - Haliza, Nurul; Pratama, Yoga (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This research aims to analyze the characteristics of Madyan women in the story of the Prophet Musa a.s. in Q.S. al-Qashash verses 23-28 and examines its relevance for the lives of Muslim women today. This research uses a qualitative approach based on literature study with thematic interpretation method (maudhu'i) through the al-Farmawi approach. The research results show that Madyan women are represented as active and rational moral subjects, with four main characters. First, maintaining one's honor (ḥaya') as the foundation of personal ethics, which is reflected in attitudes, social positions and cross-gender interaction patterns. Second, communicative intelligence which is seen in the ability to read social contexts, convey information effectively, and respond to situations proportionally and meaningfully. Third, objectivity in decision making, especially in work and marital relations, which is characterized by the use of moral and professional criteria. Fourth,an attitude of trust and social responsibility, which is reflected in the willingness to carry out public roles without ignoring ethical boundaries and self-respect. This finding confirms that the Qur'anic narrative about women helps shape the construction of meaning by positioning women as autonomous, rational subjects of interpretation in the production of the meaning of the Qur'an.